Strengthening Students' Independent Character through Practice and Example in Integrative PAI Learning at SD Negeri 014/XI Pelayang Raya - Nera Irma Sari; Padya Hayati; Ahmad Jamin; Oki Mitra (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to describe the strengthening of students’ independent character through habit formation and role modelling in integrated Islamic Education (PAI) lessons at SD Negeri 014/XI Pelayang Raya. This study employs a descriptive qualitative approach, with data collection techniques including observation, interviews and documentation. The results of the study indicate that the strengthening of students’ independent character is achieved through habits integrated into Islamic Education lessons, such as praying, reciting the Qur’an, praying in congregation, classroom duty, maintaining cleanliness, and completing tasks independently. Teachers’ role modelling through attitudes of discipline, responsibility, honesty, and independence plays a crucial role in shaping students’ character. The success of the programme is supported by the school’s commitment, a religious culture, parental cooperation, and student motivation, whilst the obstacles include differences in family upbringing, excessive use of electronic devices, diverse student characteristics, and limited learning time. Overall, the practice of habits and setting a good example in integrated PAI learning is effective in fostering students’ independent character.